Elastic moduli and hardness of η-Ta2N3 from nanoindentation measurements. (July 2015) - Bourguille, Judith; Brinza, Ovidiu; Tétard, Florent; Nikitin, Sergey; Zerr, Andreas
Abstract Nanoindentation testing was used to determine elastic moduli and hardness of η-Ta2N3, a novel stiff and hard high-pressure compound recoverable at ambient conditions. For a sample having porosity of 14% we confirmed densification of its upper layer induced by mechanical polishing: At depths <?CDATA <400 nm ?> <inline-graphic xlink:href="ark:/27927/pgj2j74g7s4" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> we obtained <?CDATA 10% ?> <inline-graphic xlink:href="ark:/27927/pgj2j74g7pg" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> higher reduced elastic modulus <?CDATA E_r ?> <inline-graphic xlink:href="ark:/27927/pgj2j74g7mc" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> and <?CDATA 25% ?> <inline-graphic xlink:href="ark:/27927/pgj2j74g7kt" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> higher hardness when compared with the sample without the densified layer. Using the experimental values of <?CDATA E_r= 238 GPa ?> <inline-graphic xlink:href="ark:/27927/pgj2j74g7j8" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> and of porosity we derived the shear modulus of dense η-Ta2N3 to be <?CDATA G_0=124-144 GPa ?> <inline-graphic xlink:href="ark:/27927/pgj2j74g7hq" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />. Hardness of the porous η-Ta2N3 was measured to be 18 GPa and its fracture toughness estimated to exceed <?CDATA 3.2 MPa· m^1/2 ?> <inline-graphic xlink:href="ark:/27927/pgj2j74g7g5" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />. The Pugh criterion suggests a high malleability of η-Ta2N3 which could explain the observed surface densification.